Non-canonical Functions of Macroautophagy Proteins During Endocytosis by Myeloid Antigen Presenting Cells - Münz, Christian (Frontiers in Immunology, 2018)
Endocytosis by myeloid antigen presenting cells such as dendritic cells and macrophages regulates both antigen processing and major histocompatibility complex (MHC) molecule trafficking during antigen presentation. The molecular machinery of macroautophagy, a catabolic pathway that delivers cytoplasmic constituents to lysosomal degradation, has recently been found to modulate both MHC class I internalization and phagocytosis of antigens for efficient MHC class II presentation. In this review, I will discuss the respective studies and how these alternative pathways of macroautophagy protein usage differ from their canonical functions. A better understanding of these additional functions of the macroautophagy machinery should allow us to interpret biological effects of macroautophagy protein deficiencies more comprehensively and to therapeutically target the different pathways which utilize the molecular machinery of macroautophagy.